MANAGING LITERACY AND NUMERACY PROGRAMS BASED ON EDUCATIONAL REPORT ANALYSIS: A CASE STUDY AT SD SUMBER MULYO, SARANG DISTRICT, REMBANG REGENCY - Ari Pujiningsih; Ngurah Ayu Nyoman; Muhammad Prayito (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the management of literacy and numeracy programs at SD Sumbermulyo, Sarang District, Rembang Regency, based on an analysis of educational reports (Rapor Pendidikan). The research employs a qualitative approach, utilizing interviews, observations, and document analysis to evaluate the effectiveness of the programs. The findings indicate that while the school has made progress in planning and organizing literacy and numeracy programs, there are challenges in meeting the targeted competencies for students, especially in the early grades. The use of educational reports as a data-driven tool has enabled the school to identify areas of improvement and adjust the programs accordingly. However, further improvements are needed in terms of resource allocation, teacher training, and community involvement. The study contributes to the understanding of how data from educational reports can enhance the planning and evaluation of educational programs in primary schools.